PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN MANDIRI BELAJAR SISWA KELAS V MUATAN PENDIDIKAN PANCASILA DI SDN KRASAK 01 - Annisa Loylya Nuzralita; Yasin; Didik Tri Setiyoko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the effect of the Discovery Learning learning model on the ability to think critically and independently learn in the Class V Pancasila Education subject at SDN Krasak 01. This research uses a quantitative approach with experimental research methods. The population subjects used were all students in class VA as the experimental class and VB as the control class. To determine whether or not there is an influence on students' critical thinking and independent learning abilities, a t test is carried out using the independent sample t test technique. From the test results for students' critical thinking abilities, data was obtained. From the results of the t test that had been carried out, the significance value for critical thinking abilities was 0.013 < 0.05 with tcount = 2.608 while ttable = 2.028 so 2.608 > 2.028. Once Ho is rejected and Ha is accepted, there is an influence on the use of the learning model in the Discovery Learning model on students' critical thinking abilities. And when we obtained the data from the t test for independent ability, we obtained a significance value of 0.043 > 0.05, we obtained a value of tcount = 2.084, while ttable = 2.020, so Ho was rejected and Ha was accepted because tcount > ttable. There is an influence of the use of learning models in the Discovery Learning model on students' independent learning abilities.